STUDY-FROM-HOME PROGRAM: MOTIVATIONAL BELIEFS OF COLLEGE STUDENTS IN THE ONLINE LEARNING ENVIRONMENT - Sari, Fatimah Mulya (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
The new learning program of study-from home amidst the COVID-19 outbreaks urges most all level students to do online learning for their learning process. It attracts a diverse range of students with different learning motivations and prior experiences. This present study is aimed to investigate the students’ motivational beliefs in online learning, in particular focusing on how students’ motivational aspects of persistence values, self-efficacy, and test anxiety for taking online learning courses affect their learning behaviors and employments of motivated learning strategies. Applying a descriptive qualitative, investigation of the motivational beliefs of 186 online learners at the tertiary level, the questionnaire consisting of 34 statements was distributed to all participants. The findings detected that motivated learning strategies covering three substantial aspects of persistence values, self-efficacy, and test anxiety shaped how the students conceptualized the purpose of online learning and affected their perceptions of the learning process.